Pengaruh Debt To Equity Ratio dan Current Ratio Terhadap Return On Asset Pada PT Sido Muncul, Tbk - Irmala, Terry Luana; Nurulrahmatiah, Nafisah; Juwani, Juwani (Jurnal Ekonomi, Bisnis dan Manajemen, 2025)
This study aims to analyze the effect of the Debt to Equity Ratio (DER) and Current Ratio (CR) on Return on Assets (ROA) at PT Sido Muncul Tbk for the period 2019–2023. The research employs a quantitative associative approach using secondary data obtained from the company’s annual financial reports. The analytical method applied is multiple linear regression with the assistance of SPSS version 26. Prior to hypothesis testing, the model was examined using classical assumption tests, including normality, multicollinearity, heteroscedasticity, and autocorrelation tests. The results show that DER has a positive and significant effect on ROA, indicating that a proportional increase in debt utilization can enhance company profitability. Similarly, CR has a positive and significant effect on ROA, implying that maintaining healthy liquidity strengthens asset efficiency. Simultaneously, DER and CR significantly influence ROA with a coefficient of determination (R²) of 0.887, meaning that 88.7% of profitability variation is explained by these two variables. These findings confirm that balancing capital structure and liquidity is a key determinant in improving financial performance within Indonesia’s pharmaceutical sector.